Healthy and unhealthy plant‐based diets in relation to the incidence of colorectal cancer overall and by molecular subtypes. Issue 8 (23rd August 2022) - Wang, Fenglei; Ugai, Tomotaka; Haruki, Koichiro; Wan, Yi; Akimoto, Naohiko; Arima, Kota; Zhong, Rong; Twombly, Tyler S.; Wu, Kana; Yin, Kanhua; Chan, Andrew T.; Giannakis, Marios; et al.
Abstract: Background: Plant‐based foods have been recommended for health. However, not all plant foods are healthy, and little is known about the association between plant‐based diets and specific molecular subtypes of colorectal cancer (CRC). We examined the associations of healthy and unhealthy plant‐based diets with the incidence of CRC and its molecular subtypes. Methods: While 123 773 participants of the Nurses' Health Study and the Health Professionals Follow‐up Study had been followed up (3 143 158 person‐years), 3077 of them had developed CRC. Healthy and unhealthy plant‐based diet indices (hPDI and uPDI, respectively) were calculated using repeated food frequency questionnaire data. We determined the tumoural status of microsatellite instability (MSI), CpG island methylator phenotype (CIMP), and BRAF and KRAS mutations. Results: Higher hPDI was associated with lower CRC incidence (multivariable hazard ratio [HR] comparing extreme quartiles, 0.86, 95% confidence interval [CI]: 0.77, 0.96; P ‐trend = .04), whereas higher uPDI was associated with higher CRC incidence (multivariable HR comparing extreme quartiles, 1.16, 95% CI: 1.04, 1.29; P ‐trend = .005). The association of hPDI significantly differed by KRAS status ( P ‐heterogeneity = .003) but not by other tumour markers. The hPDI was associated with lower incidence of KRAS ‐wildtype CRC (multivariable HR comparing extreme quartiles, 0.74, 95% CI: 0.57, 0.96; P ‐trend = .004) but not KRAS ‐mutant CRC ( P ‐trend = .22). Conclusions: While unhealthy plant‐based diet enriched with refined grains and sugar is associated with higher CRC incidence, healthy plant‐based diet rich in whole grains, fruits and vegetables is associated with lower incidence of CRC, especially KRAS ‐wildtype CRC. Abstract : An unhealthy plant‐based diet rich in refined grains and sugar is associated with higher CRC incidence. A healthy plant‐based diet rich in whole grains, fruits and vegetables is associated with lower incidence of CRC, especially KRAS ‐wildtype CRC. Replacing refined grains with healthy plant foods such as whole grains, fruits and vegetables is associated with lower CRC incidence.